Community formation in socially enabled wireless networks. (c2018) - Hakla, Mohammad (2018)
Data offloading through opportunistic device-to-device (D2D) communications constitutes a promising solution in 5G wireless networks to enable low latency communications and improved quality of experience. D2D leverages prevalent low-power and ISM-band technologies to augment existing infrastructure-based wireless systems to achieve significant increase in effective bit rates. There exist, nonetheless, various challenges that hinder the proliferation of D2D communications in public settings mainly due to interference, privacy and trust concerns. This thesis employs social relations, retrieved from social media sources, among users in close proximity to form communities of trusted users and exchange services of interest over D2D connections. To do so, a hierarchical framework composed of physical, social, and service layers is formed based on geographical proximity, social ties, and mutual interests among users. Each user forms own community intended to provide the highest number of services in a trusted environment. Multiple community formations may take place until no further service exchanges are expected. Performance results show that notable data may be offloaded from an infrastructure-based network with high trust levels set among D2D users leading to reduced mobile network congestion, savings in energy consumption, and improved user quality.